ANALYSIS OF THE FACTORS AFFECTING ECONOMIC GROWTH IN INDONESIA FROM 2005-2021 - Arien Juliana; Daryono Soebagiyo (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2023)
The purpose of this study was to determine the effect of exports, tax revenues and the rupiah exchange rate on economic growth in Indonesia in 2005-2021. This study uses time series data in the form of exports, tax revenues, and exchange rates in 2005-2021. This study uses secondary data sourced from the Central Bureau of Statistics, Bank Indonesia. Then the data is processed using the Eviews 10 application, after which the data is processed using the OLS (Ordinary Least Square) regression analysis tool and using the classic assumption test. By showing that the analysis of the Coefficient of Determination is 60.3% that exports, tax revenues and the exchange rate affect Indonesia's economic growth by 60.3% while the remaining 39.7% is influenced by variables or other factors not included in this research model